Kewajiban Notaris Terhadap Titipan Sertipikat Yang Disita Dalam Tindak Pidana Pencucian Uang - Caroline Kusyanti Winoto (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
Notaries as public officials have an important role in preventing money laundering crimes. One of the Notary's obligations is to maintain the confidentiality and security of documents submitted or entrusted to him, including certificates confiscated in the crime of money laundering. In this journal, the author discusses the notary's obligation to deposit certificates confiscated in suspected money laundering by using analytical descriptive writing methods. The results of the analysis show that the Notary has the obligation to report the alleged Crime of Money Laundering to the Financial Transaction Reports and Analysis Center (PPATK) and not to make any transactions with the certificate, except for the authorities. Notary's obligation to deposit certificates confiscated in the Crime of Money Laundering is very important in preventing the occurrence of this crime, because it will greatly cause polemic against the Notary's position which creates a dilemma. Keywords: Notary Obligations; Safekeeping of Certificates; Asset Confiscation; TPPU.